Emerging Roles for Mesencephalic Astrocyte-Derived Neurotrophic Factor (MANF) in Pancreatic Beta Cells and Diabetes - Danilova, Tatiana; Lindahl, Maria (Frontiers in Physiology, 2018)
Mesencephalic astrocyte-derived neurotrophic factor (MANF) was originally identified as a secreted trophic factor for dopamine neurons in vitro. It protects and restores damaged cells in rodent models of Parkinson’s disease, brain and heart ischemia, spinocerebellar ataxia and retina in vivo. However, its exact mechanism of action is not known. MANF is widely expressed in most human and mouse organs with high levels in secretory tissues. Intracellularly, MANF localizes to the endoplasmic reticulum (ER) and ER stress increases it’s expression in cells and tissues. Furthermore, increased MANF levels has been detected in the sera of young children with newly diagnosed Type 1 (T1D) diabetes and Type 2 (T2D) diabetic patients. ER stress is caused by the accumulation of misfolded and aggregated proteins in the ER. It activates a cellular defense mechanism, the unfolded protein response (UPR), a signaling cascade trying to restore ER homeostasis. However, if prolonged, unresolved ER stress leads to apoptosis. Unresolved ER stress contributes to the progressive death of pancreatic insulin-producing beta cells in both T1D and T2D. Diabetes mellitus is characterized by hyperglycemia, caused by the inability of the beta cells to maintain sufficient levels of circulating insulin. The current medications, insulin and antidiabetic drugs, alleviate diabetic symptoms but cannot reconstitute physiological insulin secretion which increases the risk of devastating vascular complications of the disease. Thus, one of the main strategies in improving current diabetes therapy is to define and validate novel approaches to protect beta cells from stress as well as activate their regeneration. Embryonic deletion of the Manf gene in mice led to gradual postnatal development of insulin-deficient diabetes caused by reduced beta cell proliferation and increased beta cell death due to increased and sustained ER stress. In vitro, recombinant MANF partly protected mouse and human beta cells from ER stress-induced beta cell death and potentiated mouse and human beta cell proliferation. Importantly, in vivo overexpression of MANF in the pancreas of T1D mice led to increased beta cell proliferation and decreased beta cell death, suggesting that MANF could be a new therapeutic candidate for beta cell protection and regeneration in diabetes.